Bioluminescent enzyme immunoassay for cortisol by exploitation of single-chain variable fragment and single-chain variable fragment-nanoluciferase fusion protein - Xiping Cui; Qiyi He; Huiyi Yang; Mingxia Lin; Suqing Zhao; Yunping Mu (Analytica Chimica Acta, 2026)

Hydroclimatic trend and millennial abruptions in southwestern China since the last deglaciation - Yan Yang; Hai Xu; Jing Wang; Ye Yang; Yunping Song; Jin Zhang; Siwei Shi; Yanpeng Li; Lin Shi; Kaiyang He; Yu Feng; Sheng Xu (Global and Planetary Change, 2026)

Trace volatile sulfur compounds in biogases from sanitary landfill site: emission level, toxicity, and mitigation measure - Tong Gao; Jinlong Li; Lin Li; Yanjie Wang; Jingyun Ge; Yunping Han (Journal of Cleaner Production, 2026)

Interannual variability of summertime cross-isobath exchanges in the northern South China Sea: ENSO and riverine influences - Yunping Song; Yuxin Lin; Peng Zhan; Zhiqiang Liu; Zhongya Cai (Ocean Science, 2025)
This study, combining long-term observations and high-resolution simulations, investigates the interannual variability of summer shelf circulation in the Northern South China Sea (NSCS) from 2000 to 2022. We elucidate the responses of NSCS shelf circulation to ENSO and Pearl River Estuary (PRE) freshwater runoff, revealing distinct spatial and mechanistic signatures. During El Niño years, a pronounced sea level anomaly dipole forms between the central and southern South China Sea, intensifying northward geostrophic currents in the southern basin and modulating Kuroshio intrusions. Simultaneously, an amplified PRE plume extends eastward to the 100 m isobath, markedly reducing nearshore salinity. Analysis of depth-integrated vorticity equations indicates that the pressure gradient force – driven by the joint effect of baroclinicity and bottom relief (JEBAR) and bottom pressure gradients – governs NSCS circulation variability. In coastal regions, cross-isobath velocity anomalies are primarily controlled by bottom stress curl and nonlinear vorticity advection, whereas JEBAR dominates offshore dynamics beyond the 100 m isobath. During El Niño summers, bottom density anomalies generate positive cross-isobath velocity anomalies through JEBAR, partially offset by negative anomalies from altered vertical stratification, sustaining a meandering shelf current. These results highlight the interplay of regional and remote forcings, advancing understanding of NSCS hydrographic dynamics.

Airborne human-associated ARGs in municipal wastewater treatment plants - Ying Wang; Yunping Han; Lin Li; Jianwei Liu; Hongyu Tian (Journal of Hazardous Materials, 2025)

Aerosol particles released from grit chambers of nine urban wastewater treatment plants in typical regions: Fugitive characteristics, quantitative drivers, and generation process - Wenwen Wang; Kaixiong Yang; Lin Li; Yunping Han (Water Research, 2025)

A case study of numerical simulation on the interaction among random waves, double caisson composite breakwater and seabed - Junwei Liu; Lin Cui; Yunping Jia; Honglei Sun (Ocean Engineering, 2025)

Occurrence characteristics, removal efficiencies and potential health risks of typical viruses in rural domestic sewage: A review - Yingming Zhu; Su Xu; Yu Zhou; Xuesong Guo; Yunping Han; Jun Zhan; Lin Li; Junxin Liu (Journal of Water Process Engineering, 2025)

Preparation of a novel organic-inorganic composite sludge bioflocculant (SBF) from dewatered sludge as raw material: Characteristics, flocculation mechanism and application for domestic sewage - Jingyun Ge; Hongyu Tian; Lin Li; Yunping Han; Jianwei Liu (Bioresource Technology, 2025)

Global diversity of airborne pathogenic bacteria and fungi from wastewater treatment plants - Ying Wang; Wenwen Wang; Xuezheng Yu; Zixuan Wang; Ziyu Zhou; Yunping Han; Lin Li (Water Research, 2024)

Thermal oxidation mechanism of palmitic aicd - Yunping Yao; Zhiyuan Qiang; Meng Zhang; Jia Lin; Changmo Li (Food Research International, 2024)

Potential pathogenic microorganisms in rural wastewater treatment process: Succession characteristics, concentration variation, source exploration, and risk assessment - Jun Zhan; Su Xu; Yingming Zhu; Yunping Han; Lin Li; Junxin Liu; Xuesong Guo (Water Research, 2024)

Delineation of urban growth boundary based on FLUS model under the perspective of land use evaluation in hilly mountainous areas - Yunping Zhang; Jianping Lin; Yimin Huang; Zebin Chen; Chenhui Zhu; Hao Yuan (Journal of Mountain Science, 2024)

The response and factors of microbial aerosol emission from the sludge bio-drying process - Ying Wang; Lin Li; Jiawei Ma; Yunping Han (Waste Management, 2024)

A Novel Retrograde AAV Variant for Functional Manipulation of Cortical Projection Neurons in Mice and Monkeys - Yefei Chen; Jingyi Wang; Jing Liu; Jianbang Lin; Yunping Lin; Jinyao Nie; Qi Yue; Chunshan Deng; Xiaofei Qi; Yuantao Li; Ji Dai; Zhonghua Lu (Neuroscience Bulletin, 2024)

Numerical Analysis of Dynamic Response and Liquefaction Phenomena in Sandy Seabed Foundation around a Semi-Circular Breakwater under Wave Loading - Junwei Liu; Yunping Jia; Lin Cui; Honglei Sun; Xu Lv; Mohsen Saleh Asheghabadi (Journal of Marine Science and Engineering, 2023)
Understanding the stability of the seabed foundation holds paramount significance in guaranteeing the safety and structural soundness of the breakwater alongside additional offshore structures. This study aimed to investigate the stability of a sandy seabed foundation around a semi-circular breakwater under wave loading in nearshore areas. A coupled numerical model of waves, a semi-circular breakwater, and the seabed was developed based on the OpenFOAM platform. The VARANS equations were used to govern the wave behavior. Meanwhile, the Biot’s partially dynamic model was employed to numerically simulate the seabed response considering both consolidation under self-weight and dynamic response under wave loading. The effects of various wave parameters, seabed properties, and the radius of the structure on the dynamic response of the seabed and the depth of liquefaction were investigated. The numerical results indicate that an increase in wave height, period, and permeability coefficient intensifies the dynamic response of the seabed soil. Furthermore, an increase in water depth weakened the soil’s dynamic response. There was a negative correlation between the radius of the semi-circular breakwater and the dynamic response. The influence of Poisson’s ratio on the dynamic response of the seabed was relatively small. Furthermore, a stronger dynamic pore pressure response was observed at the connection between the semi-circular breakwater and the rubble foundation.

Escape and functional alterations of microbial aerosol particles containing Pseudomonas sp. during wastewater treatment - Wenwen Wang; Lin Li; Yanjie Wang; Ying Wang; Yunping Han; Jiawei Ma; Fengguang Chai (Environmental Research, 2023)

Distribution characteristics and potential risks of bacterial aerosol in waste transfer station - Jiawei Ma; Yunping Han; Lin Li; Junxin Liu (Journal of Environmental Management, 2023)

Emission behavior and impact assessment of gaseous volatile compounds in two typical rural domestic waste landfills - Pengyu Li; Jiawei Ma; Lin Li; Yunping Han; Tianlong Zheng; Ying Wang; Fengguang Chai; Junxin Liu (Journal of Environmental Management, 2023)

Pyrroloquinoline quinone ameliorates liver injury in mice induced by cyclophosphamide - Li Qian; Fei Yang; Xinhui Lin; Su Jiang; Yun Zhang; Yunping Tang (Environmental Science and Pollution Research, 2022)

Resequencing 93 accessions of coffee unveils independent and parallel selection during Coffea species divergence - Lifang Huang; Xiaoyang Wang; Yunping Dong; Yuzhou Long; Chaoyun Hao; Lin Yan; Tao Shi (Plant Molecular Biology, 2020)

Genetic Diversity and Population Structure of Coffee Germplasm Collections in China Revealed by ISSR Markers - Lin Yan; Collins Ogutu; Lifang Huang; Xiaoyang Wang; Hua Zhou; Yulan Lv; Yuzhou Long; Yunping Dong; Yuepeng Han (Plant Molecular Biology Reporter, 2019)

Microbial population structure in near-ground aerosols during fog-haze days in northern China - Yunping Han; Mengzhu Zhang; Lin Li; Junxin Liu (Air Quality, Atmosphere & Health, 2017)

Analysis of chemical characteristics of PM2.5 in Beijing over a 1-year period - Zhanshan Wang; Dawei Zhang; Baoxian Liu; Yunting Li; Tian Chen; Feng Sun; Dongyan Yang; Yunping Liang; Miao Chang; Liu Yang; Anguo Lin (Journal of Atmospheric Chemistry, 2016)

Site-related and seasonal variation of bioaerosol emission in an indoor wastewater treatment station: level, characteristics of particle size, and microbial structure - Wenjie Ding; Lin Li; Yunping Han; Jianzhong Liu; Junxin Liu (Aerobiologia, 2016)

Mapping Quantitative Trait Loci for Omega-3 Fatty Acids in Asian Seabass - Jun Hong Xia; Grace Lin; Xiaoping He; Bu Yunping; Peng Liu; Feng Liu; Fei Sun; Rongjian Tu; Gen Hua Yue (Marine Biotechnology, 2014)

Assessing genetic structure, diversity of bacterial aerosol from aeration system in an oxidation ditch wastewater treatment plant by culture methods and bio-molecular tools - Lin Li; Yunping Han; Junxin Liu (Environmental Monitoring and Assessment, 2013)

Performance and Bacterial Community Diversity of a Full-Scale Biofilter Treating Leachate Odor in a Sanitary Landfill Site - Lin Li; Yunping Han; Junxin Liu (Water, Air, & Soil Pollution, 2012)

Microbial structure and chemical components of aerosols caused by rotating brushes in a wastewater treatment plant - Yunping Han; Lin Li; Junxin Liu; Mengzhu Zhang (Environmental Science and Pollution Research, 2012)

Impacts of global emissions of CO, NO x , and CH4 on China tropospheric hydroxyl free radicals - Mingfeng Su; Yunping Lin; Xinqiang Fan; Li Peng; Chunsheng Zhao (Advances in Atmospheric Sciences, 2012)

Knockdown of the prion gene expression by RNA interference in bovine fibroblast cells - Shaohua Wang; Xiaoqing Lv; Kun Zhang; Tonghui Lin; Xiaofang Liu; Jing Yuan; Yunping Dai; Ning Li (Molecular Biology Reports, 2010)

A High CO Episode of Long-Range Transport Detected by MOPITT - Chunsheng Zhao; Li Peng; Xuexi Tie; Yunping Lin; Chengcai Li; Xiangdong Zheng; Yuanyuan Fang (Water, Air, & Soil Pollution, 2007)

The MYB Transcription Factor Superfamily of Arabidopsis: Expression Analysis and Phylogenetic Comparison with the Rice MYB Family - Chen Yanhui; Yang Xiaoyuan; He Kun; Liu Meihua; Li Jigang; Gao Zhaofeng; Lin Zhiqiang; Zhang Yunfei; Wang Xiaoxiao; Qiu Xiaoming; Shen Yunping; Zhang Li; et al. (Plant Molecular Biology, 2006)

Sequence variations in the transcriptional regulatory region and intron1 of HLA-DQB1 gene and their linkage in southern Chinese ethnic groups - Yunping Xu; Qingsong Hu; Zehuan Liu; Yang Shen; Xiaoyi Liu; Bin Lin; Yuping Wu; Shangwu Chen; Anlong Xu (Immunogenetics, 2005)